Genomics‐based higher classification of the species‐rich hairstreaks (Lepidoptera: Lycaenidae: Eumaeini). (8th March 2022) - Robbins, Robert K.; Cong, Qian; Zhang, Jing; Shen, Jinhui; Busby, Robert C.; Faynel, Christophe; Duarte, Marcelo; Martins, Ananda R. P.; Prieto, Carlos; Lamas, Gerardo; Grishin, Nick V.
Abstract: We propose a higher classification of the lycaenid hairstreak tribe Eumaeini – one of the youngest and most species‐rich butterfly tribes – based on autosome, Lepidopteran Z sex chromosome and mitochondrial protein‐coding genes. The subtribe Neolycaenina Korb is a synonym of Callophryidina Tutt and subtribe Tmolusina Bálint is a synonym of Strephonotina K. Johnson, Austin, Le Crom, & Salazar. Proposed names are Rhammina Prieto & Busby, new subtribe ; Timaetina Busby & Prieto, new subtribe ; Atlidina Martins & Duarte, new subtribe ; Evenina Faynel & Grishin, new subtribe ; Jantheclina Robbins & Faynel, new subtribe ; Paiwarriina Lamas & Robbins, new subtribe ; Cupatheclina Lamas & Grishin, new subtribe ; Parrhasiina Busby & Robbins, new subtribe ; Ipideclina Martins & Grishin, new subtribe ; and Trichonidina Duarte & Faynel, new subtribe . Phylogenetic results from the autosome and Z sex chromosome analyses are similar. Future analyses of datasets with hundreds of terminal taxa may be more practical time‐wise by focussing on the smaller number of sex chromosome sequences (2.6% of nuclear protein‐coding sequences). The phylogenetic classification and biological summaries for each subtribe suggest that a variety of factors affected Eumaeini diversification. About a dozen kinds of male secondary sexual organs with frequent evolutionary gains and losses occur in Atlidina, Evenina and Jantheclina (141 species combined). Females have been shown to use these organs to discriminate between conspecific and nonconspecific males, facilitating sympatry among close relatives. Eumaeina, Rhammina and Timaetina (140 species combined) are overwhelmingly montane with some evidence for a higher incidence of sympatric diversification. Seven Neotropical lineages in five subtribes invaded the temperate parts of the Nearctic Region with a diversification increase in the Callophryidina (262 species). North American Satyrium and Callophrys then invaded the Palearctic at least once each, with a major species‐richness increase in Satyrium . The evolution of litter‐feeding detritivores within Calycopidina (172 species) resulted in an increase in diversification rate compared with its flower‐feeding sister lineage. Atlidina, Strephonotina, Parrhasiina and Strymonina (562 species combined) each contain a mixture of genera that specialize on one or two caterpillar food plant families and genera that are polyphagous. These would be appropriate subtribes to assess how the breadth of caterpillar food plants and the frequency of host shifts affected diversification. Abstract : More than 1, 300 species of Eumaeini hairstreak butterflies evolved in less than 30 million years. We propose a subtribe classification based on analysis of 13.87 million autosomal ("diploid" inheritance) and 368 thousand Z sex chromosomes ("haplo‐dipnoid" inheritance) with protein‐coding base pairs. More than 90% of the species have male secondary sexual organs on the head, wings, legs, or abdomen. Ecologically, there is a recurrent pattern of food plant specialization and generalization, with one large lineage feeding in the leaf‐litter. Biogeographically, two eumaeine lineages diversified primarily in the Andes, with an apparent high rate of sympatry among sister lineages. The Nearctic biogeographic realm has been repeatedly colonized from the Neotropics, with subsequent colonizations of the Palearctic.